MEMPERSIAPKAN DAYA SAING LULUSAN PROGRAM STUDI PERBANKAN SYARIAH MELALUI KURIKULUM KKNI - Yosy Arisandy (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
The rapid growth and development of sharia financial institutions (especially Islamic banks) have apositive impact on the increasing demand for human resources (HR) sharia. To meet the needs ofqualified, professional, and sharia human resources in accordance with the needs and expectations ofthe Islamic finance industry, the participation of various parties is required. One of the highcontributing parties is Islamic religious college (PTAI) through Islamic economics majors. Islamiceconomics majors must play an active role in preparing qualified and professional Islamic sharia so asto meet the needs and expectations of the Islamic finance industry. In building the competitiveness ofgraduates of Islamic Banking Prodi can be supported through KKNI curriculum with stages: 1.Determining the profile of graduates, 2. Creation of Learning Outcomes formulation consisting ofstages Material Selection (Extent, Depth, Level of ability to be achieved), Matrix of learningachievement study materials, the concept of subject and the amount of SKS, 3. Concept integratedcourses and the end result of curriculum structure and instructional design (new curriculum document).